Genome-wide investigation and expression profiles of the NPF gene family provide insight into the abiotic stress resistance of Gossypium hirsutum - Liu, Juanjuan; Wang, Caixiang; Peng, Jialuo; Ju, Jisheng; Li, Ying; Li, Chaozhou; Su, Junji (Frontiers in Plant Science, 2023)
Membrane transporters encoded by NITRATE TRANSPORTER 1/PEPTIDE TRANSPORTER (NPF) genes, which play crucial roles in plant growth, development and resistance to various stresses, are involved in the transport of nitrate (NO3-) and peptides. In several plant species, NPF genes are involved in the resistance to abiotic stresses; however, whether the whole NPF gene family in cotton contributes to this resistance has not been systematically investigated. Here, 201 genes encoding NPF proteins with a peptide transporter (PTR) domain were confirmed in three different Gossypium species, namely, Gossypium hirsutum, Gossypium arboreum and Gossypium raimondii. The NPF proteins in these three Gossypium species and Arabidopsis thaliana were classified into three different subfamilies via phylogenetic analysis. Among the genes that encode these proteins, most GhNPF genes in the same subfamily contained similar gene structures and conserved domains. Predictions of the promoters of these genes revealed that the cis-acting elements included phytohormone- and light-responsive elements, indicating that some of these genes might be expressed in response to abiotic stress. Furthermore, 52 common potential candidate genes in 98 GhNPFs were predicted to exhibit specific spatiotemporal expression patterns in different tissues based on two RNA sequencing (RNA-seq) datasets. Finally, the gene expression profiles of abiotic stress indicated that 31 GhNPF genes were upregulated in at least one treatment period. Under abiotic stress for 12 and 24 h, the expression of GhNPF8 was upregulated upon cold treatment but downregulated with heat treatment, salt treatment and drought treatment. Furthermore, the expression of genes GhNPF8, GhNPF54 and GhNPF43 peaked at 6 h after heat and salt treatment. These results indicated that these genes exhibit underlying characteristics related to responses to abiotic stress. The verification of NPFs and analysis of their expression profiles in different tissues and in response to different abiotic stresses of cotton provide a basis for further studying the relationship between abiotic stress resistance and nitrogen (N) transport in cotton, as well as identifying candidate genes to facilitate their functional identification.